2018
DOI: 10.2147/ott.s182005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressing lncRNA <em>SNHG16</em> inhibited HCC proliferation and chemoresistance by functionally sponging hsa-miR-93

Abstract: BackgroundLong noncoding RNAs (lncRNAs) have been identified as prognostic biomarkers and functional regulators in human cancers. The present study aimed to determine the expressions and functions of an lncRNA, Small Nucleolar RNA Host Gene 16 (SNHG16), in hepatocellular carcinoma (HCC).Patients and methodsSNHG16 expressions were tested by quantitative real-time PCR (qRT-PCR) in HCC cell lines, as well as 43 pairs of HCC tissues and pair-matched healthy hepatic tissues. It was overexpressed in Hep3B and HuH7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 30 publications
2
80
0
Order By: Relevance
“…On the contrary, Xu et al showed that SNHG16 acted as an antioncogene in hepatocellular carcinoma. SNHG16 was expressed at a lower level in the cancerous tissue than normal tissue, and SNHG16 could alleviate 5‐FU resistance . Liu J et al showed that SNHG20 played an oncogenic role in liver cancer, and promoted the EMT pathway in cancer progression …”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%
“…On the contrary, Xu et al showed that SNHG16 acted as an antioncogene in hepatocellular carcinoma. SNHG16 was expressed at a lower level in the cancerous tissue than normal tissue, and SNHG16 could alleviate 5‐FU resistance . Liu J et al showed that SNHG20 played an oncogenic role in liver cancer, and promoted the EMT pathway in cancer progression …”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%
“…9,10 For example, the lncRNA GHET1 promotes HCC cell proliferation and can predict poor prognosis in HCC via inhibiting KLF2. 12 In addition, knockdown of ANRIL is able to repress HCC progression through modulating miR-122-5p. 12 In addition, knockdown of ANRIL is able to repress HCC progression through modulating miR-122-5p.…”
Section: Introductionmentioning
confidence: 99%
“…11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93. 12 In addition, knockdown of ANRIL is able to repress HCC progression through modulating miR-122-5p. 13 It has been evidenced that LINC00346 is upregulated in several cancers and can play oncogenic roles.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Xu et al . found SNHG16 performed antitumor effects by inhibiting cell proliferation and chemoresistance in hepatocellular carcinoma . Thus, it is necessary for us to detect the roles of SNHG16 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…22 SNHG16 exerted oncogenic function in glioma by regulating miR-4518/PRMT5 regulatory axis to promote cell viability and inhibit cell apoptosis in the report by Lu et al 23 Additionally, Xu et al found SNHG16 performed antitumor effects by inhibiting cell proliferation and chemoresistance in hepatocellular carcinoma. 24 Thus, it is necessary for us to detect the roles of SNHG16 in NSCLC. In this study, SNHG16 was found to be upregulated in NSCLC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%